2015
DOI: 10.3109/13697137.2015.1007123
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in VDR gene in Tunisian postmenopausal women are associated with osteopenia phenotype

Abstract: The ApaI polymorphism showed an association with osteopenia and low-impact vertebral fracture incidence but not with osteoporosis. The TaqI polymorphism is associated specifically with the osteopenia phenotype. The presence of the two polymorphisms increases the risk to develop osteopenia in postmenopausal Tunisian women. Osteopenia seems to be genetically determined. However, osteoporosis is the result of interaction between genetic and environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…In a large cohort of Iranians, Fok1 A/G (rs2228570) polymorphism was significantly associated with OP in postmenopausal women [45]. Sassi et al [46] analyzed the association of other VDR polymorphisms (ApaI and TaqI) with BMD in postmenopausal Tunisian women and an increased risk to develop osteopenia, but not OP, was shown which strengthens the hypothesis that OP results from the interaction of genetic and environmental factors. The relationship of the 21 single nucleotide polymorphisms (SNP) in 7 selected candidate genes (LRP5, RANK, RANKL, ESR1, VDR, P2XR7, and OPG) with BMD at different body sites was evaluated in an Iranian population [47].…”
Section: Non-modifiable Risk Factors Modifiable Risk Factorsmentioning
confidence: 75%
“…In a large cohort of Iranians, Fok1 A/G (rs2228570) polymorphism was significantly associated with OP in postmenopausal women [45]. Sassi et al [46] analyzed the association of other VDR polymorphisms (ApaI and TaqI) with BMD in postmenopausal Tunisian women and an increased risk to develop osteopenia, but not OP, was shown which strengthens the hypothesis that OP results from the interaction of genetic and environmental factors. The relationship of the 21 single nucleotide polymorphisms (SNP) in 7 selected candidate genes (LRP5, RANK, RANKL, ESR1, VDR, P2XR7, and OPG) with BMD at different body sites was evaluated in an Iranian population [47].…”
Section: Non-modifiable Risk Factors Modifiable Risk Factorsmentioning
confidence: 75%
“…Aa (ApaI) genotype was considered as a protective factor against osteoporosis while aa genotype was considered as an osteopenic factor related to bone fractures. In addition, Aa/TT genotype (ApaI/TaqI) was the major haplotype in individuals with normal bone mass (27). In Belarusian osteoporetic menopausal women, ApaI, TaqI, and BsmI polymorphisms were found to be an influencing factors of osteoporosis (28).…”
Section: Discussionmentioning
confidence: 99%
“…For BsmI total 65 studies with 6,880 cases and 8,049 controls were found eligible to include in the meta-analysis . For ApaI total 31 studies with 3,763 cases and 3,934 controls were found to be eligible to include in the meta-analysis [19,23,25,33,39,40,43,46,51,58,59,61,64,66,68,70,72,74,76,[78][79][80][82][83][84][85][86][87][88][89][90]. For FokI meta-analysis total 18 studies with 1,895 cases and 1,722 controls were found eligible to include in the meta-analysis [33, 40,45,51,56,62,65,66,68,70,74,76,79,[91][92][93][94][95].…”
Section: Eligible Studiesmentioning
confidence: 99%